SOCIAL REPRESENTATIONS ELABORATED BY NURSING STUDENTS ABOUT COVID-19 PREVENTION - Rêgo Neta, Marly Marques; Sousa Neto, Antonio Rosa de; Carvalho, Ana Raquel Batista de; Almeida, Rosângela Nunes; Valle, Andréia Rodrigues Moura da Costa; Moura, Maria Eliete Batista; Freitas, Daniela Reis Joaquim de (Cogitare Enfermagem, 2023)
Objective: to understand the social representations elaborated by nursing students about the prevention of COVID-19. Method: exploratory-descriptive and qualitative research. Data were produced through interviews with 32 participants, conducted in the period from September 2021 to July 2022. The Study Setting was a public higher education institution, located in the northeastern region of Brazil. Data were processed using IRaMuTeQ software. Results: the genesis of the social representations of COVID-19 prevention pointed to two axes: Organization of ideas about COVID-19 prevention measures, and Efficiency, reliability and source of the information obtained. Final Considerations: the social representations showed the knowledge about the prevention measures of COVID-19, provided an opportunity to clarify the origin of the students’ knowledge and the specificities they consider important. It is hoped that this study can serve as a foundation for further research and/or interventions with nursing students.